Mini-review: Neuroprotection by astrocytes in brain ischemia: importance of microRNAs - Ouyang, Yi-Bing (2013)
Astrocytes have been shown to protect neurons and increase their survival in many pathological settings. Manipulating astrocyte functions is thus an important strategy to enhance neuronal survival and improve outcome following cerebral ischemia. Increasing evidence supports the involvement of microRNAs (miRNA), some of them being astrocyte-enriched, in the regulation of cerebral ischemia. This mini review will focus on several recently reported astrocyte-enriched miRNAs (miR-181 and miR-29 families and miR-146a), their validated targets, regional expression and effects on outcome after cerebral ischemia.